Portions of the Book of Common Prayer together with hymns and addresses in Eskimo [electronic resource] - Church of England.; Walton, W. G. (William Gladstone); Peck, E. J. (Edmund James), 1850-1924. (London : Society for Promoting Christian Knowledge, 1900)
Electronic reproduction. Mode of access: Internet. 44